2021
DOI: 10.1101/2021.09.06.459131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of the SHP-1 activity by PKC-θ regulates NK cell activation threshold and cytotoxicity

Abstract: Natural Killer (NK) cells play a crucial role in immunity, killing virally infected and cancerous cells. The balance of signals initiated upon engagement of activating and inhibitory NK receptors with cognate ligands determines killing or tolerance. Nevertheless, the molecular mechanisms regulating rapid NK cell discrimination between healthy and malignant cells in a heterogeneous tissue environment are incompletely understood. The SHP-1 tyrosine phosphatase is the central negative NK cell regulator, which dep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 82 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…Ben-Shmuel et al demonstrated that protein kinase c theta (PKC-θ) phosphorylates the S591 residue of SHP-1, maintaining SHP-1 in the inactivated, "dormant" state [37]. Accordingly, silencing PKC-θ reactivates SHP-1, consequently reducing NK cell cytotoxicity and promoting cancer progression [37]. These results reinforced the tumor-suppressive impact of blocking SHP-1 activity.…”
Section: Shp-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Ben-Shmuel et al demonstrated that protein kinase c theta (PKC-θ) phosphorylates the S591 residue of SHP-1, maintaining SHP-1 in the inactivated, "dormant" state [37]. Accordingly, silencing PKC-θ reactivates SHP-1, consequently reducing NK cell cytotoxicity and promoting cancer progression [37]. These results reinforced the tumor-suppressive impact of blocking SHP-1 activity.…”
Section: Shp-1mentioning
confidence: 99%
“…Even though the strategy employed by SHP-1 to negatively regulate NK cell activation has been investigated for a relatively long period of time, it was not until very recently that how the regulatory pathway of SHP-1 itself was discovered. Ben-Shmuel et al demonstrated that protein kinase c theta (PKC-θ) phosphorylates the S591 residue of SHP-1, maintaining SHP-1 in the inactivated, "dormant" state [37]. Accordingly, silencing PKC-θ reactivates SHP-1, consequently reducing NK cell cytotoxicity and promoting cancer progression [37].…”
Section: Shp-1mentioning
confidence: 99%